Andexanet alfa effectively reverses edoxaban anticoagulation effects and associated bleeding in a rabbit acute hemorrhage model - Lu, Genmin (PLoS One, 2018)
INTRODUCTION: Increasing use of factor Xa (FXa) inhibitors necessitates effective reversal agents to manage bleeding. Andexanet alfa, a novel modified recombinant human FXa, rapidly reverses the anticoagulation effects of direct and indirect FXa inhibitors. OBJECTIVE: To evaluate the ability of andexanet to reverse anticoagulation in vitro and reduce bleeding in rabbits administered edoxaban. MATERIALS AND METHODS: In vitro studies characterized the interaction of andexanet with edoxaban and its ability to reverse edoxaban-mediated anti-FXa activity. In a rabbit model of surgically induced, acute hemorrhage, animals received edoxaban vehicle+andexanet vehicle (control), edoxaban (1 mg/kg)+andexanet vehicle, edoxaban+andexanet (75 mg, 5-minute infusion, 20 minutes after edoxaban), or edoxaban vehicle+andexanet prior to injury. RESULTS: Andexanet bound edoxaban with high affinity similar to FXa. Andexanet rapidly and dose-dependently reversed the effects of edoxaban on FXa activity and coagulation pharmacodynamic parameters in vitro. In edoxaban-anticoagulated rabbits, andexanet reduced anti-FXa activity by 82% (from 548±87 to 100±41 ng/ml; P<0.0001), mean unbound edoxaban plasma concentration by ~80% (from 100±10 to 21±6 ng/ml; P<0.0001), and blood loss by 80% vs. vehicle (adjusted for control, 2.6 vs. 12.9 g; P = 0.003). The reduction in blood loss correlated with the decrease in anti-FXa activity (r = 0.6993, P<0.0001) and unbound edoxaban (r = 0.5951, P = 0.0035). CONCLUSION: These data demonstrate that andexanet rapidly reversed the anticoagulant effects of edoxaban, suggesting it could be clinically valuable for the management of acute and surgery-related bleeding. Correlation of blood loss with anti-FXa activity supports the use of anti-FXa activity as a biomarker for assessing anticoagulation reversal in clinical trials.